BALINESE CULTURE IN EAT, PRAY, LOVE ELIZABETH GILBERT - Trikaloka Handayani Putri (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2011)
Trikaloka Handayani Putri University of Pesantren Tinggi Darul ‘Ulum Jombang princessnaura@yahoo.com Abstract This article would discuss about the reflection of Balinese culture in Eat Pray, Love Elizabeth Gilbert. This novel becomes phenomenal since the positive critics appear. The ending of this novel, Elizabeth told her memory about Bali, her way to describe Bali was very ‘realistic’. So many cultural aspects described in this novel. This writing will be developed through the cultural study theory as the fundamental in the study of Eat, Pray, Love Novel. key words: cultural study, cultural aspects   Abstrak Artikel ini membahas tentang budaya Bali yang tergambar dalam novel Eat, Pray, Love tulisan Elizabeth Gilbert. Novel ini begitu fenomenal semenjak kritik positif bermunculan. Dibagian akhir novel ini, Elizabeth menyampaikan memorinya tentang Bali, cara dia menggambarkan Bali begitu nyata. Banyak Aspek budaya yang tergambar dalam novel ini. Tulisan ini akan dikembangkan melalui teori study budaya sebagai kerangka utama dalam mempelajari novel Eat, Pray, Love. kata kunci: studi kultural, aspek budaya